Upaya Peningkatan Pembelajaran Lompat Jauh Gaya Jongkok Dengan Bermain Lompat Rintangan Pada Siswa Kelas V SDN Tanjungrejo Tahun Ajaran 2024/2025 Kecamatan Buluspesantren Kabupaten Kebumen - Puput Widodo; Arif Budiman (Mathematics Education Study Program, 2025)
Problems faced by PJOK teachers in delivering material on the basic movements of the long jump squatting style. The goal to be achieved is to increase the learning of squat style long jump among elementary school students using the medium of playing hurdles. This research is classroom action research (PTK). Classroom action research is carried out through four stages, namely (1) Developing a plan, (2) taking action, (3) making observations, and (4) reflecting. The instruments used in this research were observation blanks during and after the learning process. The observation blank contains indicators of the learning class atmosphere and long jump skill results. The research subjects were 22 students in class V of SD Negeri Tanjungrejo, Bulus Pesantren District, Kebumen Regency, consisting of 9 male students and 13 female students. The results of the research show that long jump learning carried out using an obstacle jumping play approach can increase students' activeness and basic long jump movements, namely starting, pushing off and landing. The activity results from cycle I to cycle II were 95% of children in the good category, 5% in the sufficient category and for the development of basic long jump movements, 86% of children were in the good category, 14% of children were in the sufficient category. 91% of children are in the good category, 9% of children are in the fair category. Meanwhile, 86% of children were in the good category, 14% of children were in the fair category.